GENDER EQUALITY ISSUES IN THE ARCHITECTURE PROFESSION - Rika Triyunia Savitri (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2021)
This article discusses gender equality in the architectural profession. A number of studies that have been conducted by previous researchers show that architects are a profession that is famous for its macho culture which is dominated by men. Women who are involved in this profession still experience discrimination and barriers to work. This article discusses gender equality in the architectural profession, both in a narrative and in the world of practice. This article uses a qualitative descriptive method by referring to a literature review through several online references, one of which is Google Scholar, which was published from 2015 to 2022. The results of the literature review, it can be concluded that there is still a gender gap in the architectural profession. Nevertheless, several female architectural figures who can prove that women have produced architectural works that are not inferior to male architects. Of course, in the process of gender equality, female architects are faced with several obstacles and problems that occur in the world of practice such as inappropriate work wages, the occurrence of sexism, and inappropriate working hours. Keywords:Gender Equality, Architect